2015
DOI: 10.1007/s10072-015-2227-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 gene polymorphisms with sporadic Parkinson’s disease in a Han Chinese population

Abstract: Parkinson's disease (PD) is considered as a multifactorial disorder involving complex interactions between genetic and environmental factors, while previous studies point to a pivotal role of neuroinflammation in the pathophysiology of PD. As a member of pattern recognition receptors, TLR4 plays an important role in the immune response and inflammatory responses. Growing evidences suggest that mutation of TLR4 gene may be connected with the development of PD. The objective of this study was to evaluate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…Interestingly, CD4 + T‐helper (T H ) cells, particularly T H 1 cells, are increased in the peripheral blood of PD patients (Baba et al, 2005) and T H 1 cells recruit CD8 + cytotoxic T cells which are the predominant T‐cell infiltrate in the brain in PD patients at post‐mortem and in MPTP‐lesioned animals (Brochard et al, 2009), providing further support for an adaptive CD4 + T H cell mediated immune response in PD. Further evidence is emerging for a possible role of the adaptive immune in the development of Parkinson's disease as toll‐like receptor 4 (TLR4) gene polymorphisms have been linked to sporadic Parkinson's disease (Zhao et al, 2015) and α‐synuclein can induce the up‐regulation of TLRs (Beraud et al, 2011). Additionally, ablation of TLR4 provided neuroprotection in the MPTP‐model of PD (Noelker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD4 + T‐helper (T H ) cells, particularly T H 1 cells, are increased in the peripheral blood of PD patients (Baba et al, 2005) and T H 1 cells recruit CD8 + cytotoxic T cells which are the predominant T‐cell infiltrate in the brain in PD patients at post‐mortem and in MPTP‐lesioned animals (Brochard et al, 2009), providing further support for an adaptive CD4 + T H cell mediated immune response in PD. Further evidence is emerging for a possible role of the adaptive immune in the development of Parkinson's disease as toll‐like receptor 4 (TLR4) gene polymorphisms have been linked to sporadic Parkinson's disease (Zhao et al, 2015) and α‐synuclein can induce the up‐regulation of TLRs (Beraud et al, 2011). Additionally, ablation of TLR4 provided neuroprotection in the MPTP‐model of PD (Noelker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the frame of PD, TLR4 knockout animals are less vulnerable to dopamine depletion induced by MPTP treatment, at least in the striatum, suggesting a role for TLR4-related neuroinflammation in PD (Conte et al, 2017), possibly associated with a decrease in Cer levels. In addition to upregulation of TLRs in PD brains, TLR4 gene polymorphisms are associated with sporadic PD in a Chinese population (Zhao et al, 2015). Interestingly, Cer synthesis is a requisite for the TLR4-induced insulin resistance and the activation of TLR4 is able to induce insulin resistance in certain brain regions (i.e., the hypothalamus) (Holland et al, 2011).…”
Section: Role Of Ceramides In the Cellular Metabolism Of The Brain Anmentioning
confidence: 99%
“…The TLR4-MyD88 signaling pathway was involved in the upregulation of miR-873 and the downregulation of ABCA1 following LPS treatment. A recent study has shown that polymorphisms in the TLR4 gene are associated with sporadic PD and early-onset PD [33]. miR-873 transfection or ABCA1 silencing induced the accumulation of α-synuclein in lysosomes, suggesting that alteration of the intracellular cholesterol transporter can impair the clearance of α-synuclein.…”
mentioning
confidence: 99%